Fārān se Karbalā tak - Zubairī, Bilāl (Jhang Adabī Ikāḍimī, 1972)
Early history of Islam, with particular reference to the martyrdom of Husayn ibn Ali at Karbala, Iraq, in 680; includes a description of the anniversary observances in various parts of the world.